Electronic Structure of Dodecyl Syringate Radical Suitable for ESR Molecular Quantum Computers - Tamulienė, J.; Tamulis, A.; Kulys, J. (Nonlinear Analysis: Modelling and Control, 2004)
The neutral radical of dodecyl syringate is suggested as a candidate for molecular Electron Spin Resonance (ESR) quantum computers. The first principle of quantum chemical calculations indicates that this molecule with a stable delocalised electron spin may represent a qubit in quantum information processing. The spin density analysis exhibits that unpaired spin of the radical is delocalised in the region of not-compensated valence bond. Isotropic Fermi contact coupling constants and anisotropic spin dipole couplings was investigated and indicated the largest hyperfine splitting (HFS) of ESR spectra on atoms of the above mentioned region of not-compensated valence bond.